H2O2-Responsive Nanoparticle Based on the Supramolecular Self-Assemble of Cyclodextrin - Zhenqiang Dong; Zhenqiang Dong; Yang Kang; Qijuan Yuan; Manli Luo; Zhipeng Gu (Frontiers Media S.A., 2018)
Designing stimuli responsive, controllable and biocompatible multifunctional nanoparticles is an important progress in the current quest for drug delivery systems. Herein, we devoted to developing a β-cyclodextrin (β-CD) based drug delivery nanoparticles (NPs) that release Bovine serum albumin (BSA) via glucose-responsive gate. The design involves synthesis of sodium alginate with β-CD modified (Alg-β-CD) and methoxypolyethylene glycol (mPEG-Fc) containing ferrocene (Fc) uncharged end-capping. When α-cyclodextrin (α-CD) was added with these two segments, the stable non-covalent supramolecular structure of Alg-β-CD/mPEG-Fc/α-CD can be self-assembled into NPs in aqueous solution. BSA loaded Alg-β-CD/mPEG-Fc/α-CD also has been prepared. Interestingly, these supramolecular Alg-β-CD/mPEG-Fc/α-CD/BSA NPs showed uniform sphere structure and constant BSA loading content. Also, this new kind of NPs can disassemble in the present of hydrogen peroxide (H2O2). Since glucose oxidase (GOD) can oxidize glucose and produce H2O2, so this kind of polymeric NPs can also have glucose responsive behavior in the GOD containing environment. Developed functional Alg-β-CD/mPEG-Fc/α-CD might be a promising drug delivery strategy for diabetes or immunotherapy with more efficiency.